Long-term follow up of a tuberous sclerosis patient: evaluation of anti-epileptic drugs and self- management support therapy - Anindya Diwasasri; Retno Danarti; Retno Sutomo; Sunartini Hapsara (Paediatrica Indonesiana, 2020)
Tuberous sclerosis (TSC) (OMIM 191100) is an inherited, autosomal dominant disorder affecting multiple organ systems.1 A genetic mutation in one of the tumor suppressor gene (TSG) alleles causes tumor growth in various organ systems. Tuberous sclerosis can be found in people of all races, and does not differ in men and women, with an incidence 1 in 6,000 births and prevalence of 1 in 20,000.1-3 Although the prevalence is quite high, diagnosing this disorder is often difficult and delayed due to diverse disease manifestations and varied age at onset.